EUTECTIC CEMENTITE PHASE ELIMINATING PROCESS IN NODULAR CAST IRON WITH PEARLITE MATRIX - Ladiva Taris, Adabina
Cars require an engine to convert thermal energy into kinetic energy, and when performing its function, the engine is assisted by a camshaft. Ductile cast iron is used as the material for making the camshaft due to its properties of wear resistance, toughness, and ease of production at a low cost. Generally, the ductile cast iron used in camshafts has a pearlitic matrix. However, in a particular case, there is an abnormal phase called eutectic cementite in nodular cast iron that supposed to be in pearlitic phases. In this experiment, the process of eliminating the eutectic cementite phase in solid condition using heat treatment. The heat treatment is carried out at two different temperature holding variations, which are 850°C and 950°C, for a duration of 20 hours, followed by cooling in ambient air. The results of the thermal treatment are analyzed in terms of microstructure and hardness. The findings of the experiment indicate that the eutectic cementite phase can be eliminated through solid-state heat treatment. Additionally, the heat treatment also influences the amount of graphite, area fraction of each phase, and hardness. However, heat treatment does not affect on the nodularity level.